Stimulation of Numerical Skills in Children with Visual Impairments Using Image Recognition - Taquía Gutiérreza, J. A. (2021)
The learning process in training children with visual impairments and low vision requires the use of new devices that integrate image recognition and feedback on stimulation sequences with the senses of tactile and auditory responses into their design. Eighteen students with visual impairments (blind or low vision) between the ages of eight and twelve, who attend a school specialized in teaching children with visual impairments, completed three numerical stimulation routines. The software developed evaluates skills of addition and subtraction, identification of geometric shapes, and mental calculations to achieve a goal. The results of the test showed that the students performed better in the game dynamic than in the addition and subtraction routines. This study is a contribution to designing software for low-cost devices as it has been verified that this type of application works on both a laptop and a Raspberry pi device.